Hebrew Exegesis Online Using Information Technology to Enhance Biblical Language Study - Klipowicz, Steven W. (Teaching theology and religion, 1999)
Information technology is bringing change to theological education. Computer-mediated instruction has been employed for teaching basic factual materials and for providing study resources. Information technology has been helpful as an instructional aid using the drill and practice format, but how can it promote learning in more complex areas of knowledge acquisition such as analysis, synthesis, and creative judgment? Gordon-Conwell Theological Seminary in Charlotte, N.C. developed an online course to teach Hebrew exegesis. A theory-driven pedagogy was employed that used a Web-based instructional design to promote asynchronous learning, collaborative projects, and peer review. This article presents the rationale and design for the class, a narrative of the class experience, and an evaluation of results. Outcomes of the class experience and suggestions for application of technology to other subject areas are included.